Visual short-term memory deficits in REM sleep behaviour disorder mirror those in Parkinson's disease. - Rolinski, M; Zokaei, N; Baig, F; Giehl, K; Quinnell, T; Zaiwalla, Z; Mackay, C; Husain, M; Hu, M (Oxford University Press, 2016)
Individuals with REM sleep behaviour disorder are at significantly higher risk of developing Parkinson's disease. Here we examined visual short-term memory deficits-long associated with Parkinson's disease-in patients with REM sleep behaviour disorder without Parkinson's disease using a novel task that measures recall precision. Visual short-term memory for sequentially presented coloured bars of different orientation was assessed in 21 patients with polysomnography-proven idiopathic REM sleep behaviour disorder, 26 cases with early Parkinson's disease and 26 healthy controls. Three tasks using the same stimuli controlled for attentional filtering ability, sensorimotor and temporal decay factors. Both patients with REM sleep behaviour disorder and Parkinson's disease demonstrated a deficit in visual short-term memory, with recall precision significantly worse than in healthy controls with no deficit observed in any of the control tasks. Importantly, the pattern of memory deficit in both patient groups was specifically explained by an increase in random responses. These results demonstrate that it is possible to detect the signature of memory impairment associated with Parkinson's disease in individuals with REM sleep behaviour disorder, a condition associated with a high risk of developing Parkinson's disease. The pattern of visual short-term memory deficit potentially provides a cognitive marker of 'prodromal' Parkinson's disease that might be useful in tracking disease progression and for disease-modifying intervention trials.